2019
DOI: 10.3390/su11061557
|View full text |Cite
|
Sign up to set email alerts
|

Do Firm and Entrepreneur Characteristics Play a Role in SMEs’ Sustainable Growth in a Middle-Income Economy like Côte d’Ivoire?

Abstract: Globally, small- and medium-sized enterprises (SMEs) play a key role in driving sustainable economic growth in both developed and developing countries. The main objective of this study was to investigate the firm and entrepreneur characteristics influencing the growth of SMEs in Côte d’Ivoire, with special insight into why this country has been a middle-income economy for decades despite its numerous economicpotentialities. Through IBM SPSS version 22.0, 19 hypotheses were tested using data from 160 SMEs opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
20
2
4
Order By: Relevance
“…It is known that the principal learning channel is the school, which forms part of the education system. A previous study by Diabate et al [6] revealed that the level of education (known to be a fundamental developmental factor) does not play an invaluable role in SMESG in Côte d'Ivoire. This is the inevitable consequence of the weak education system (compared to education systems in developed countries).…”
Section: Which Entrepreneurs' Abilities Are Affecting the Growth Of Imentioning
confidence: 93%
See 4 more Smart Citations
“…It is known that the principal learning channel is the school, which forms part of the education system. A previous study by Diabate et al [6] revealed that the level of education (known to be a fundamental developmental factor) does not play an invaluable role in SMESG in Côte d'Ivoire. This is the inevitable consequence of the weak education system (compared to education systems in developed countries).…”
Section: Which Entrepreneurs' Abilities Are Affecting the Growth Of Imentioning
confidence: 93%
“…Since it is evidenced that SME growth may be influenced by the business sector [80], business size [6] and entrepreneurs' work experience [81], these characteristics could be considered as control variables (CV). Figure 1 represents a concise conceptualization of EA and EO, leading to SMESG.…”
Section: Conceptual Modelmentioning
confidence: 99%
See 3 more Smart Citations